2018
DOI: 10.1016/j.envres.2018.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Critical age windows in the impact of lifetime smoking exposure on respiratory symptoms and disease among ever smokers

Abstract: Among ever smokers, smoking exposure in each stage of the lifespan show persistent harmful effects for adult respiratory health, while women appeared to be more vulnerable to an early age of smoking debut and amount of smoking in adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
0
10
0
1
Order By: Relevance
“…Table 1 summarizes the characteristics of each study. The association between risk of adult COPD and childhood serious respiratory infections, pneumonia or bronchitis was reported in 14 studies 6,7,15,16,[20][21][22][23][24][25][26][27][28]50 ; childhood asthma in nine studies 8,15,16,20,28,[34][35][36][37] ; maternal smoking in seven studies 6,15,18,19,23,37,41,51 ; CETS in two studies 40,41 ; child maltreatment in five studies [29][30][31][32][33] ; low birth weight in three studies 6,23,39 ; and premature birth in three studies. 23,28,39 Included participants were older than 40 years, except for studies from the European Community Respiratory Health Survey, in which the average age was about 36 years.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 summarizes the characteristics of each study. The association between risk of adult COPD and childhood serious respiratory infections, pneumonia or bronchitis was reported in 14 studies 6,7,15,16,[20][21][22][23][24][25][26][27][28]50 ; childhood asthma in nine studies 8,15,16,20,28,[34][35][36][37] ; maternal smoking in seven studies 6,15,18,19,23,37,41,51 ; CETS in two studies 40,41 ; child maltreatment in five studies [29][30][31][32][33] ; low birth weight in three studies 6,23,39 ; and premature birth in three studies. 23,28,39 Included participants were older than 40 years, except for studies from the European Community Respiratory Health Survey, in which the average age was about 36 years.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…23,28,39 Included participants were older than 40 years, except for studies from the European Community Respiratory Health Survey, in which the average age was about 36 years. 8,26,51 The study population of five studies was eversmokers 21,23,34,41,51 and two studies included neversmokers. 6,7 Table S1 in the Supporting Information shows the assessment of article quality.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…The smoking population underestimates their respiratory symptoms; however, exercise activity is many times reduced. Therefore, to detect new COPD cases, questions related to respiratory vulnerability and deconditioning are required 27,35 . Besides, recent studies showed that exacerbations are frequent in smokers, even they had normal spirometry tests.…”
Section: Discussionmentioning
confidence: 99%
“…As described in a systematic review covering 16 studies of 69,365 individuals, tobacco exposure in utero and early life represents an important risk factor for development of COPD in adulthood ( Savran and Ulrik, 2018 ). In addition, among ever smokers, people with an early age of smoking debut appeared to be more vulnerable to pulmonary respiratory symptoms ( Erbas et al, 2018 ). Cigarette smoking has also been shown to augment the adverse effects of early life exposures (infant respiratory infection and home overcrowding) ( Allinson et al, 2017 ) on mid life FEV1 and FVC.…”
Section: Well-established Risk Factorsmentioning
confidence: 99%